Pengaruh model creative problem solving terhadap pencapaian kompetensi fisika siswa kelas XI SMAN 1 2x11 Enam Lingkung pada materi keseimbangan benda tegar dan elastisitas - Fadli Andrias; yurnetti yurnetti; gusnedi gusnedi; ratnawulan ratnawulan (Universitas Negeri Padang, 2019)
Achievement of Physics Competence of students in class XI of SMA N 1 2X11 Enam Lingkung has not reached the minimum completeness criteria, this is due to several things namely the lack of student interest in learning. For this reason, a study was conducted to look at the effect of the Creative Problem Solving learning model on the achievement of physics competence in class XI students. This research uses quasi-experimental research with Randomized Control Group Only Design. The study population was all students of class XI SMA N 1 2X11 Enam Lingkung who were enrolled in semester 1 of Academic Year 2019/2020. Sampling was done by using the Random Sampling Cluster technique. Research data includes student physics competencies on aspects of knowledge and skills. Based on data analysis that has been done on two aspects. Both sample classes are normally distributed and have a homogeneous variance, so the two similarity test is done with the t test. the achievement of knowledge competency tcount = 2.09 and ttable = 2.00, while the skills value tcount = 2.19 and ttable = 2.00. From the achievement of competencies in both aspects, it is obtained tcount> t table, then tcount is located outside the area of acceptance of Ho, which means Hi is accepted. Based on the t-test at the 0.05 level, it can be stated that there is a significant influence of the use of the Creative Problem Solving model on the achievement of physics competence of class XI students.